2007
DOI: 10.1016/j.otohns.2007.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing before and after Tonsillectomy as Evaluated by Surface Electromyography

Abstract: The reported sEMG method and obtained data might be further used: 1) As an additional tool for comparison of different methods of tonsillectomy (eg, cold vs hot dissection, laser surgery, etc); 2) For further development of objective postsurgical pain assessment; 3) As an additional tool for assessment and development of less traumatic surgical technique; and 4) For monitoring of recovery in difficult cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…Our patient did suffer to some degree with oropharyngeal pain and dysphagia for roughly 3 weeks after surgery. This type of recovery is similar to that described in the setting of adult tonsillectomy [22]. Other authors have discussed need for speech language rehabilitation in select cases after transoral retropharyngeal and parapharyngeal approaches.…”
Section: Discussionsupporting
confidence: 73%
“…Our patient did suffer to some degree with oropharyngeal pain and dysphagia for roughly 3 weeks after surgery. This type of recovery is similar to that described in the setting of adult tonsillectomy [22]. Other authors have discussed need for speech language rehabilitation in select cases after transoral retropharyngeal and parapharyngeal approaches.…”
Section: Discussionsupporting
confidence: 73%
“…The palatine tonsils are closely associated with the aforementioned nervous plexus and muscles. It is well known that surgical intervention and haemostatic manipulations may affect these structures [14,16]. An open wound is created in the palatine fossa after tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This membrane is replaced by advancement of the adjacent mucosa within 3 weeks after tonsillectomy. It has been reported that PTP is caused by inflammation of the tonsillary bed, nerve irritation and the spasm of exposed pharyngeal muscles [14,[16][17][18][19]. The pain is not completely relieved until the muscles were covered with the adjacent mucosa [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It highlights the repetition of a movement or a function of a muscle or muscle group 4,10,11,13,18,20,26,29,[40][41][42][43][44][45][46][47] .…”
Section: -2 -Electromyographymentioning
confidence: 99%